Company from the Uncanny Valley: A Psychological Perspective on Social Robots, Anthropomorphism and the Introduction of Robots to Society - Samuel, Janina Luise (ETHICS IN PROGRESS, 2019)
There are many issues surrounding the introduction of social robots into society, including concerns about how they may be used to replace true social interaction in personal life, dehumanise formerly social occupations such as elderly care, and be perceived as more human than they actually are. This paper shall present a psychological perspective on the human reception of social robots and apply the gathered information to address these concerns.